O processo criativo de um livro ilustrado: uma experiência em artes visuais (Revista Apotheke, 2020)
Picture books are cultural productions that mix visual and oral language in the same structure. The illustration is intended to suggest new readings and interpretations from what the reader is seeing, instigating the imagination. In order to understand this relationship between text and image, a clipping is presented about what an illustration should do, what its role in the picture book is and what is needed to it. Children’s literature is another point addressed in this research in art, as well as the organization and the arrangement of elements in the layout designing process. This work’s focus is on the creative process of the picture book The White Chicken, considering how it was thought, executed, and recorded. Thus, the theoretical study about the covered topics comes in response to the practical experiences, dissolving the boundaries of these two aspects of the research.
Keywords: ilustration; picture book; children's literature; creative process